Redesain Dies Proses Blank-Pierce dengan Penyesuaian Mesin Press Guna Meningkatkan Efisiensi Produk Reinforcement Quarter Panel Extension RH/L - Desy Agustin; Ibnu Syihab; Sanurya Putri Purbaningrum; Abdul Wahid Arohman; Indra Rizki Pratama (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The redesign of the die design in the blank-pierce process for the RH/LH quarter panel extension reinforcement product was carried out using field observations to obtain actual data. The production process consists of five stages: blanking, piercing, restriking, bending and forming. Meanwhile, in the redesign process, the RH/LH quarter panel extension reinforcement product is evaluated in the blanking and piercing die processes. Cycle time analysis after the tool design has been redesigned shows the potential for increasing efficiency by reducing process time. MPP data is used as a guide for die design with relevant machine specifications, die size and materials. Machine pressure and tonnage calculations were carried out for the current die design and the revised version, showing significant improvements in production efficiency. The die redesign was carried out to increase output per stroke and to use more sophisticated automation processes. The results of this research show that improved die design can increase production efficiency and productivity by reducing the number of strokes required and properly adjusting machine capacity.